On Skew Triangular Matrix Rings (Communications in Mathematical Research, 2021)
Let $α$ be a nonzero endomorphism of a ring $R$, $n$ be a positive integer and $T_n(R, α)$ be the skew triangular matrix ring. We show that some properties relatedto nilpotent elements of $R$ are inherited by $T_n(R, α)$. Meanwhile, we determine thestrongly prime radical, generalized prime radical and Behrens radical of the ring $R[x; α]/(x^n)$, where $R[x; α]$ is the skew polynomial ring.